The Use of AI in Supporting Neurodivergent Students: A Multilingual Classroom Study - Yousra Lahmiyed; Khadija Anasse; Najib Slimani (Yayasan Visi Intan Permata, 2025)
This study examines the effectiveness of AI tools’ integration into inclusive multilingual classroom settings, specifically in helping neurodivergent students. Research has shown that many students with Asperger’s Syndrome often face difficulties with language and social interaction, especially in multilingual classrooms. These challenges not only affects their academic performance but also hinders their ability to connect with others. This study explores how Artificial Intelligence (AI) can be used to support Neurodivergent students, with a focus on a particular group of Asperger’s Syndrome, through tools that are sensitive to language needs and tailored to individual learning profiles. The study conducted its research in a Moroccan private multilingual school, specifically in the region of Tangier-Tetouan-Al Hoceima, and draws on a mix of both qualitative and quantitative methods. It focuses on how AI tools; such as language learning apps, speech-to-text programs, and adaptive learning platforms, can support inclusion and engagement in the classroom. Moreover, data was gathered through case studies, interviews with teachers and parents, and classroom observations. Preliminary findings have shown that AI tools can support students in understanding language, improving their communication skills, and becoming more active in their learning. Teachers have also noticed that students responded positively to personalized learning experiences offered through AI and became more autonomous. These results suggest that AI has positively impacted education into a more inclusive setting by offering flexible and accessible support, especially for neurodivergent learners. This study also emphasizes the need for educational policies that recognize the value of technology in diverse classrooms. It offers practical insights for creating learning environments that are more responsive, equitable, and supportive for all students.